KOLABORASI MATERI PERKULIAHAN DENGAN INDUSTRI DAN PENGARUHNYA TERHADAP PENINGKATAN KOMPETENSI MAHASISWA (Survey pada Mahasiswa Akademi Pariwisata Siliwangi) - Kustini, E. Yuyun (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This research is motivated by the existence of hospitality expertise courses that are not in accordance with the demands of the industrial world, so that students feel difficulties during street vendors, such as students' lack of understanding of the equipment used. This study aims to determine the effect of collaboration between courses and industry on improving student competence. This research is a survey research with a quantitative approach, the data from the distribution of questionnaires is analyzed using path analysis, because the researcher wants to know the effect of each dimension of course collaboration with industry on improving student competence. The results of data processing with the Excell and SPSS programs showed that the collaboration of subjects with industry had a very strong effect on improving student competence with a contribution of 74.17% and the remaining 25.83% was influenced by other variables not studied. Partially, the strategy dimension in the collaboration variable has the greatest influence on increasing student competence, and the smallest influence is on the dimension of the institutional structure.